Cosmological entanglement of initial multipartite states - Xiao-Ying Jiang; Xiao-Li Huang; Shu-Min Wu (European Physical Journal C: Particles and Fields)
Abstract In this study, we investigate the intricate interplay between the entanglement entropy of initial multipartite states characterized by a nonzero particle number q and the dynamics of an expanding universe. Our analysis demonstrates that spacetime expansion significantly enhances the particle production rate associated with such states, yielding an amplification factor of $$q + 1 + \frac{q}{|β |^2}$$ q + 1 + q | β | 2 compared to the vacuum scenario. This result indicates that the presence of multipartite excitations in the asymptotic past leads to markedly increased cosmological particle generation in the asymptotic future. Furthermore, we show that the entanglement entropy of these states grows substantially under expansion, far surpassing the entropy arising from vacuum fluctuations alone. These findings suggest that multipartite initial states serve as highly effective probes for encoding and extracting information about the dynamical history of spacetime.